Review of the design of the helicopter rotor - Petrović, Dalibor P.; Čabarkapa, Obrad T. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This article - paper presents the design of the main rotor of the helicopter supported by the patent documents, as a very useful tool (instrument) to reach the specific ideas and design in order to find the most economical way for the quality solution for a certain technical problem present in the process of design (construction). A large amount of technical information first appears in patent documents and about two thirds of this information cannot be found on any other site. The structure of patent documents is presented with an emphasis on the elements that relate to technical information with the detailed explanation of the possibilities of the application of the patent documentation during the process of design of the main helicopter rotor. The procedure and methods of research of the related patent documents are presented on a specific example of helicopter rotor design. The Espacenet database of patent documents was used as the most comprehensive and the most frequently used database containing over eighty million different patent documents about inventions and technical improvement (advancement) from all over the world.The crucial part of the paper relates to the presentation of a patent search method in order to find a technical solution for the structures of the main helicopter rotor   which relates to the provision of the required casting and rapid response changes of accommodation angle (step) of the rigid rotor blades of helicopters. Introduction Patent documents contain the largest database of various specifications, which,  in order to preserve novelty of the innovation, first appear in patent documents three to five years earlier than in other technical reference publications. For this reason, patent documentation is an essential source of information for researchers - designers, primarily with the aim of finding structural solutions to the technical problem being solved, as well as for the monitoring and establishing new trends in the development of specific systems and equipment. Patent documentation and content of patent documents Patent documents contain technical, legal and bibliographic information to determine the patent. Technical information is of fundamental  importance to designers for understanding  the invention. If the technical information contained in the patent documents contains the solution of the specific problem to be solved, it is necessary to examine the legal basis for using this information, in order to avoid violation of intellectual property rights. Patent documents search By searching a patent documents database, an expert  in a particular field of technology is allowed to: be up to date with the latest technical and technological solutions, find ready-made solutions to specific technical problems, get ideas for starting future development, establish patent activities of competitors in the market, get insight into the trends of development in a particular technical field, assess technology offered for licensing, have a more favorable positioning during negotiations on the transfer of technology as well as a variety of other information. The application of patent documents in designing the main helicopter rotor Search and analysis of patent documents is given as an example for rigid rotors, in which the bearings are replaced by elastic elements. In terms of design, these rotors are derived by connecting the blades and the head  with elastic elements or by linking the blades with the elastic rotor head. During the design of the rotor head, advanced search for patent documents in the Espacenet basis is applied. Conclusion This article - paper emphasizes the significance of patent documents and the necessity of the search of patent documents databases, while designing the main rotor of a helicopter. The proper use of patent documents is a very useful tool for getting to specific ideas for solving specific technical problems during design. In this specific example, a technical problem related to a structural solution of the head of the rigid rotor of a helicopter, in order to provide the necessary casting and a rapid response of changes of the accommodation angle (step) of rigid rotor blades of helicopters. The basic intention of this paper is to illustrate and explain to researchers - designers that it is necessary to use patent documents in the process of design - construction.
Keywords: Patent databases; Documentation; Rotors; Patents; Helicopters